The Projected Burden of Non-Communicable Diseases Attributable to Overweight in Brazil from 2021 to 2030 - De Moraes-Ferrari, G (Nature Research, 2022)
Although studies have quantified the current burden of diseases attributable to overweight and obesity in Brazil, none have estimated its burden in the future. The study aimed to estimate the potential impact of different scenarios of changes in the prevalence of overweight on non-communicable diseases (NCD) in the Brazilian adult population until 2030. We developed a multistate life table model including 11 body mass index (BMI) related diseases to estimate attributable NCDs cases and deaths under the following scenarios of changes in overweight over a 10-year simulation: (1) the continuity of the current trajectory of BMI increases, (2) reducing the rate of increase by half, (3) stopping future BMI increases, and (4) the reduction of the prevalence of overweight by 6.7%. In Brazil, if the current trends of BMI increase are maintained from 2021 to 2030, approximately 5.26 million incident cases and 808.6 thousand deaths from NCDs may occur due to overweight. If the annual increase in overweight was reduced by half until 2030, 1.1% of new NCD cases and 0.2% of deaths could be prevented (respectively, 29,600 cases and 1900 deaths). Alternatively, if the current prevalence of overweight is maintained, as set as a national goal in Brazil until 2030, the incident NCD cases and the deaths could be reduced by respectively 3.3% (92,900) and 1.5% (12,100) compared to continuation of current trends. If the prevalence of overweight is reduced by 6.7% until 2030, 6.5% (182,200) of NCD cases and 4.2% (33,900) of deaths could be prevented. The epidemiologic burden of overweight in Brazil tends to increase if bold policy interventions are not adopted in Brazil. © 2022, The Author(s).